Tourism product quality perceptions and big spenders' travel intentions in Malaysia: a comparative study of Southeast Asian and Middle Eastern countries / Zaliha Zainuddin, Mazni Saad and Mohd Hanafi Azman Ong - Zainuddin, Zaliha; Saad, Mazni; Azman Ong, Mohd Hanafi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
Tourism has been the second-largest economic driven in Malaysia's economy. This paper aims to examine the mediating role of perceived tourism products quality (TPQ) in Malaysia towards electronic word-ofmouth (eWOM) and travelling intentions of Southeast Asia (SEA) and the Middle East. Two-fold objectives were developed: (1) To investigate the significant difference of the perception between SEA and Middle East countries on Malaysian's tourism products quality and (2) to examine the mediating role of perceived tourism products quality in Malaysia towards eWOM and travelling intentions of SEA and the Middle East. Methodology design using the SEA and Middle East tourists who have been to Malaysia was approached through the online Google Form survey. Upon processing 92 respondents from the Middle East and 79 respondents from SEA, the data sets of responses were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) and MANOVA techniques. The findings show a significant mediating effect of perceived TPQ toward the relationship of eWOM and revisit intention. Besides, comparison analysis shows that SEA tourists are more likely to revisit Malaysia than the Middle East, the same as for the finding of eWOM and perceived TPQ. TPQ has a mediating impact on eWOM and revisits intention for both markets. The findings of this study are expected would positively affect stakeholders, especially the State Tourism, Tourism Board, and tourism industry players.